Multiple cerebral venous sinus thrombosis in a young male presenting as Status epilepticus - Singh Tuteja, Harshpreet; Acharya, Sourya; Shukla, Samarth (International Journal of Medical Research and Review, 2016)
Background: Cerebral venous thrombosis is a disease with multiple etiologies that present with a remarkably wide spectrum of clinical signs and symptoms. Case report: 38 year old male presented to the emergency department with history of seizures since half hour duration. There was also a history of acute attack of gastroenteritis with multiple episodes of vomiting and diarrhea which was treated by private practitioner. CT scan brain revealed intra parenchymal bleed in left parietal region, possibility of venous infarct. Conclusion: Thrombosis of the sinuses cause intracranial hypertension and raised ICT by impairing the absorption of CSF. This may also further result in hemmorhagic cortical infact like in our case.